A case report: acute sinusitis turned into shockingly rapid sepsis at young male adult - Patrycja Brzozowska; Bianka Nowińska; Karina Lissak; Wiktoria Bińczyk; Olgierd Dróżdż; Bartosz Siudek; Anna Wiśniewska (Nicolaus Copernicus University in Toruń, 2024)
Sinusitis is a disease of usually mild course - however, sometimes secondary diseases might develop such as pneumonia which might have moderate to severe course. Pneumonia is usually treated ambulatory, regardless some patients' state worsens and they are in need of hospital treatment, sometimes even in Intensive Care Unit. In this article is presented a case of a patient with such history - a young adult with no medical history of chronic diseases, whose state worsened and required ICU treatment.